STUDI TENTANG PERUBAHAN TRADISI CANANG PADA ERA MODERNISASI DI DESA TELUK BERINGIN KECAMATAN GUNUNG TOAR KABUPATEN KUANTAN SINGINGI - Riga Yulianti; Hambali Hambali; Zahirman Zahirman (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This research is based on the change of canang tradition in the era of modernization in Teluk Beringin Village where nowadays cotton tools are not used but have been replaced with microphone loudspeakers. It used to be that all information in the government was conveyed through the canang either in order to meetings for deliberations in making certain decisions as well as for social activities but now delivered using microphone, in surau or in the mosque. Problem rumors are: (1) What aspects are changing in canang tradition in the era of modernization? (2) What factors caused the change of the canang tradition in the era of modernization? Objectives of the study (1) To know what aspects are changing in the tradition of canang in the era of modernization. (2) To know the factors that caused the change of canang tradition in the era of modernization. This research is descriptive qualitative. Data collection techniques in this study are, Observation, Documentation, Interview, Review Library, Questionnaire. The respondents of this study were the Head of Family. The sample size is 52 samples. The result of the research shows that the factors that caused the change of canang tradition in the era of modernization in Teluk Beringin Village, Gunung Toar Sub-district of Kuantan Singingi Regency are new discoveries, other cultural influences, and increase and decrease of population. And the Changing Aspects in canang Tradition in the era of modernization in Teluk Beringin Village, Gunung Toar Subdistrict, Kuantan Singingi Regency are Equipment, Working Mode, Language, Time, and Beat rhythm.Key Words: Change, Canang Tradition, Modernization.